Persepsi Mahasiswa Disabilitas Sensorik Rungu terhadap Inovasi Pembelajaran Bahasa Inggris - Dapa, Aldjon Nixon; Putra, Andi Dewangga Permana; Ismail, Ismail (Peneliti.net, 2024)
This study aims to explore the perceptions of students with Deaf Sensory Disabilities (DSR) towards English language learning innovations after the initial implementation stage. Qualitative methods were used by conducting in-depth focus group discussions involving a number of DSR students who are currently studying for higher education. The results of the study indicate that DSR students have diverse views on the English language learning innovations that have been implemented. Several key findings include: (1) an increase in learning motivation with the use of visual and interactive technology, (2) the important role of various parties in supporting learning, and (3) the need for adaptation of learning materials that are more in line with the characteristics of DSR students. Challenges identified include limited understanding of linguistic components by DSR students and lack of peer support. This study concludes that English language learning innovations have significant potential to improve learning effectiveness, but need to be adapted to the specific needs of DSR students. Implications of this study include recommendations for the development of more inclusive curricula and teaching methods in higher education.